2013
DOI: 10.1002/jcop.21580
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Race and Ethnicity in Clients’ Experiences of Mental Health Treatment

Abstract: Clinicians and researchers have pointed to the need for culturally sensitive mental health interventions. Yet it has not been determined if the inclusion of cultural elements affects the way mental health clients experience services. This study examined 102 clients who had received mental health treatment from outpatient mental health clinics to investigate whether culturally related elements involving race and ethnicity were important to clients and whether they were related to client satisfaction and perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 78 publications
(83 reference statements)
2
66
0
2
Order By: Relevance
“…Improving counselors’ race‐specific skills and knowledge could serve to more directly redress racism and its negative impacts on clientele of color (Hook et al, 2016; Owen, Tao, Imel, Wampold, & Rodolfa, 2014). In turn, experts have suggested that the general inclusion and exploration of race‐related topics in counseling can positively affect the experience of clients of color (Day‐Vines, Bryan, & Griffin, 2013; Hipolito‐Delgado & Reinders‐Saeman, 2017; Meyer & Zane, 2013; Zhang & Burkard, 2008).…”
mentioning
confidence: 99%
“…Improving counselors’ race‐specific skills and knowledge could serve to more directly redress racism and its negative impacts on clientele of color (Hook et al, 2016; Owen, Tao, Imel, Wampold, & Rodolfa, 2014). In turn, experts have suggested that the general inclusion and exploration of race‐related topics in counseling can positively affect the experience of clients of color (Day‐Vines, Bryan, & Griffin, 2013; Hipolito‐Delgado & Reinders‐Saeman, 2017; Meyer & Zane, 2013; Zhang & Burkard, 2008).…”
mentioning
confidence: 99%
“…Thus, ethnic minorities were more likely to report higher intentions and to actually seek help after controlling for sex, distress, impairment, social encouragement, stigma, attitudes, and intentions. This contrasts with past research which indicates that racial and ethnic minorities are less likely to seek psychological help and more likely to drop out of therapy (Diala et al, 2000; Substance Abuse and Mental Health Service Administration, 2015; U.S. Department of Health and Human Services, 2002), often because mental health providers do not share their ethnicity (Gamst et al, 2003;Maramba & Hall, 2002;Meyer, Zane, & Cho, 2011;Meyer & Zane, 2013;Turner, Brody & Hopps, 2008;Ward, 2005). Perhaps one possible explanation is that individuals were responding based on what they thought the researcher wanted instead of what they would really do.…”
Section: Hypothesismentioning
confidence: 77%
“…The articles coded in this category ( n = 49, 20%) examine various aspects of community mental health centers and the services they provide. For example, Flynn, Balch, Lewis and Katz () assessed client satisfaction with community mental health services; and Meyer and Zane () investigated whether culturally relevant elements of mental health treatment plans predicted client satisfaction and treatment outcomes. The dates of publication for articles in this category ranged from 1973 to 2013, with the majority ( n = 35, 71%) published prior to 1985, and only four articles published after 2000.…”
Section: Resultsmentioning
confidence: 99%